Nonsurgical Admissions With Traumatic Injury: Medical Patients Are Trauma Patients Too. Issue 3 (May 2018) - Nelson, Laura; Kuzniewski, Sally; Grossman, Michael; Yelon, Jay A.; Szydziak, Lisa
Abstract : Nontrauma service (NTS) admissions are an increasing problem as ground-level falls in elderly patients become more common. The admission and evaluation of trauma patients to nontrauma services in trauma centers seeking American College of Surgeons (ACS) verification, must follow the ACS mandates for performance improvement requiring some method of evaluating this population when admitted to services other than trauma, orthopedics, and neurosurgery. The purpose of this study and performance improvement project was to improve our process for the definition and evaluation of trauma patients who were being admitted to nontrauma services. We designed an algorithm to evaluate appropriateness of NTS admission and evaluated outcomes for NTS admissions utilizing that algorithm. We created a scoring algorithm and evaluated appropriateness of NTS admission over 2 years in a community-teaching ACS Level II trauma center. We reviewed trauma registry data using χ 2 and Fisher exact tests to determine differences in outcome for NTS versus trauma service (TS) admissions. From December 2014 to December 2016, NTS admission rate fell from maximum of 28% to 4% stabilizing between 8% and 10%. Mortality and overall complication rate between NTS and TS were similar ( p = .40 and .66, respectively), but length of stay was lower for TS admissions ( p < .0001). A scoring system of algorithm can be used to determine appropriateness of NTS admissions, and validity of the tool can be confirmed using registry-based outcome data for TS versus NTS admissions.